Assessment of toxicity of a biosurfactant from Candida sphaerica UCP 0995 cultivated with industrial residues in a bioreactor - Sobrinho, Humberto Bezerra Souza; Luna, Juliana Moura; Rufino, Raquel Diniz; Porto, Ana Lúcia Figueiredo; Sarubbo, Leonie Asfora (Electronic Journal of Biotechnology, 2013)
Background: The aim of the present study was to propose a low-cost method for the production of a biosurfactant by the yeast Candida sphaerica and assess its toxicity and phytotoxicity. The medium was formulated with distilled water supplemented with residue from a soy oil refinery (5%) and corn steep liquor (2.5%) as substrates. These two products were the sources of carbon and nitrogen as well as mineral elements to encourage the growth of the microorganism and production of a biosurfactant. Results: The isolated biosurfactant yield was 6.364 g/l. The biosurfactant exhibited an excellent ability to reduce surface tension (26 mN/m) and demonstrated no toxicity against seeds of Brassica olerace, Chicoria intybus and Solanum gilo or the microcrustacean Artemia salina employed as a bioindicator. The biosurfactant exhibited no antimicrobial activity against the fungi and bacteria tested. Conclusions: The promising results obtained in this study indicate the feasibility of producing biosurfactants from powerful non-toxic organic residues and their application in the bioremediation of contaminated soil and water.